Influence of bracket design on microbial and periodontal parameters in vivo - Jan van Gastel (Blackwell Synergy, 2007)
Aim: To compare undisturbed plaque formation on teeth bonded with different types of orthodontic brackets with non-bonded control teeth, via a de novo plaque growth experiment over a 7-day period. Material and methods: A randomized controlled trial with split-mouth design was set up enroling 16 dental students. Within each subject sites with Speeds(S) and GACs(G), brackets and control sites were followed. Clinical periodontal parameters were recorded at baseline, on days 3 and 7. Microbiological samples were taken from the brackets and the teeth on days 3 and 7. Results: Both anaerobe and aerobe colony-forming units (CFU) were significantly higher in S-sites than in G-sites (p50.0002, p50.02). The shift from aerobic to anaerobic species was observed earlier in S-sites than in G-sites. The aerobe/anaerobe CFU ratio was significantly lower in S-sites than in G-sites (p50.01). On day 3, the crevicular fluid flow was significantly higher in S-sites than in control sites (p50.01). On day 7, S-sites and G-sites showed a significantly higher crevicular flow than control sites (both po0.0001). More hypertrophy was seen in S- than in G- and control sites (p50.05). No significant differences for bleeding on probing were observed. Conclusion: Bracket design can have a significant impact on bacterial load and on periodontal parameters.